Job stress and university faculty members’ life satisfaction: The mediating role of emotional burnout - Xu, Yin; Wang, Yike (Frontiers in Psychology, 2023)
As one of the leading work-related health problems arising from increasingly fierce competition, work-related stress has become a significant predictor of the reduced wellbeing of university faculty members, especially for non-tenured junior faculty members. In light of this and based on a survey, this research seeks to examine how and why work-related stress impacts the life satisfaction level of university junior faculty members. The results indicate that the three subdivisions of university faculty members’ work-related stress, namely, research stress, teaching stress, and administrative stress, are all negatively related to their life satisfaction level. In addition, emotional burnout has been confirmed to function as the psychological mechanism for the aforementioned main effects. The research contributes to the literature mainly by offering a new insight in which the three subdivisions of work-related stress are regarded as independent variables affecting the life satisfaction level of university junior faculty members.